Influence of Storm Events on Chlorophyll Distribution Along the Oligotrophic Continental Shelf Off South-Western Australia - Chen, Miaoju; Pattiaratchi, Charitha B.; Ghadouani, Anas; Hanson, Christine (Frontiers in Marine Science, 2020)
The role of storm events in controlling chlorophyll distribution along the oligotrophic Rottnest continental shelf is examined data collected by autonomous ocean gliders combined with meteorological data. Spatial and temporal distribution of chlorophyll concentrations were obtained from a repeated transect across the shallow continental shelf that revealed complex relationships among wind events (e.g. differences in wind speed and direction) and chlorophyll concentrations. Data indicated that the water column responded rapidly to changes in wind speeds alternating between stratification, de-stratification and vice-versa over 1-3 days. Under low wind conditions (wind speeds < 7 ms-1), the water column was stratified and dense shelf water cascades (DSWC) was the dominant feature. The majority of DSWC events were associated with synchronous increases in chlorophyll and suspended sediment, often close to the seabed. During storm events (wind speeds >15 ms-1) higher chlorophyll values were present throughout the vertically mixed water column. Maximum chlorophyll concentrations, more than double that due to climatology, were observed 1-3 days after the passage of storms subsequent to sediment re-suspension. Storm events, with an onshore component, promoted downwelling, the water column retained vertical stratification, and DSWC was present across the shelf. Here, DSWC intensified with higher chlorophyll in the cascaded water extending further offshore. It is concluded that wind speed and direction are the dominant parameters controlling the distribution of chlorophyll particularly during storm events.